PENERAPAN MODEL PEMBELAJARAN NOVICK UNTUK MENCAPAI KETUNTASAN BELAJAR PESERTA DIDIK PADA MATERI LARUTAN PENYANGGA - Lisda Aprianti; Sri Haryati; Lenny Anwar (Jurnal Pendidikan Kimia Universitas Riau, 2020)
The implementation of Novick learning model has been implemented in class XI MIA SMAN 1 Kampar Timur. Ther purpose of this study is to achieve student’s mastery learning on the subject of buffer solution. The type of this research is pra-experiment research with one-shot study case design. The research data were collected from 27 March to 25 April 2019. The population in the research were class XI MIA SMAN 1 Kampar Timur. The samples were selected from the three existing classes, namely class XI MIA 4. Data analysis technique used is to calculate presentation of classical mastery learning. Based on the researth results were obtained by classical learning completeness of 77.78 % and classical indicator completeness was 80 %. This means that the application of the Novick learning model can achieve student learning completeness in the material buffer solution in class XI MIA SMA Negeri 1 Kampar Timur.